Sex education and sexuality, intuition and sensitivity: references to pedagogical practices of teachers in basic education. - Vera Márcia Marques Santos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2014)
This article is an excerpt from the systematization of doctoral research which established dialogues on continuing education, and pedagogical practices of teachers and teachers in Brazil and Portugal, where it presents speech applicant that "intuition and sensitivity" refer pedagogical practices of teachers / as regards the manifestations of sexuality in school premises. The speech that gave rise to the theory that motivated the research comes from the speech of teachers and teachers from different districts of a state in southern Brazil, from the spaces of initial training in pedagogy courses in the distance mode, where it had a student body made up of teachers that the time attending higher education. We opted for qualitative research, where one can see that the sensitivity and intuition does not replace the knowledge and training, but can be important elements for making pedagogical careful regarding the issues surrounding sexuality in the educational process.